Research progress of NAC transcription factors in woody plants - Zhang, Huan; Zhao, Jia; Zhang, Tongxing; Wang, Guiying; Han, Zhixiao; Meng, Yuemei; Bi, Jingran; Ren, Yachao; Yang, Minsheng (Frontiers in Plant Science, 2025)
The plant-specific NAC transcription factor family has the largest number of members, they are involved in regulating the entire process of plant growth and development, and the responses to biotic and abiotic stressors. This article reviews the progress regarding the elucidation of the structure and function of the NAC transcription factor family and the regulatory mechanisms through which NAC transcription factors affect various processes in woody plants, including the formation of the secondary cell wall, seed development, flowering, and fruit ripening. Additionally, this article encompasses the current research status of NAC transcription factors in response to abiotic stressors, such as salt and drought, as well as biotic stressors, such as pathogens and pests in woody plants. Most of the research is still at the stages of gene cloning, structural identification, and functional analysis; the specific downstream target genes and their molecular mechanisms remain unclear. Future research should focus on exploring unknown functions and action mechanisms, to promote an understanding of the regulatory network of NAC transcription factors in woody plants, thereby providing a theoretical basis and gene resources for research on NAC transcription factors and the creation of new forest germplasm.